Effect of IMU location on estimation of vertical ground reaction force during jumping - Kerns, Jordan A.; Zwart, Andrew S.; Perez, Pietro S.; Gurchiek, Reed D.; McBride, Jeffrey M. (Frontiers in Bioengineering and Biotechnology, 2023)
Several investigations have examined utilizing inertial measurement units (IMU) to estimate ground reaction force (GRF) during exercise. The purpose of this investigation was to determine the effect of IMU location on the estimation of GRF during vertical jumping. Eight male subjects completed a series of ten countermovement jumps on a force plate (FP). The subjects had an IMU attached to the sacrum, back and chest. GRF was estimated from data from the individual IMUs and by using a two-segment model and combined sensor approach. The peak GRF values for the sacrum, back, chest and combined IMUs were 1,792 ± 278 N, 1,850 ± 341 N, 2,054 ± 346 N and 1,812 ± 323 N respectively. The sacral IMU achieved the smallest differences for GRF estimates providing a root mean square error (RMSE) between 88 N and 360 N. The IMU on the sacrum also showed significant correlations in peak GRF (p<0.001) and average GRF (p<0.001) using the Bland-Altman 95% Limits of Agreement (LOA) when in comparison to the FP. Based on assessment of bias, LOA, and RMSE, the IMU located on the sacrum appears to be the best placement to estimate both peak and average GRF during jumping.